(untitled) (Research, Society and Development, 2020)
Introduction: trauma in the face is a prevalent situation in hospitals with urgent and emergency services. The orbital cavity is usually affected in fractures, involving bones, soft tissues and neurovascular, with an incidence of more than 40% of maxillofacial trauma. Objective: to analyze orbital traumas and their clinical repercussions, taking into account etiology and possible complications. Methodology: the study consisted of an integrative review, with original and review scientific articles indexed in the PubMed / Medline database, published over the last five years. Based on the inclusion criteria, the articles underwent careful filtering and subsequent choice, according to the emphasis on the desired information. Results and Discussion: Orbital trauma requires a thorough clinical examination and rapid diagnosis. Thus, it can be seen that diplopia, periorbital ecchymosis and enophthalmos are the most prevalent clinical findings in the studies, being caused by several etiological factors. Therefore, ophthalmological evaluations must be performed to analyze the patient’s visual conditions, allowing a more coherent approach with a better prognosis for the patient. In addition, the orbital volume varies according to the etiology and fracture patterns, which can trigger complications due to the close relationship with the eyeball. Final considerations: It is noted that the repercussions found directly influence the effectiveness of the diagnosis, the predictability of complications and the treatment plan. Therefore, it is essential for the surgeon to know how to correctly evaluate and interpret clinical findings after orbital fractures.